Analisis Strategi pada UMKM Samosa Menggunakan Model Strategi Porter’s Five Forces - Mora, Linda (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to evaluate the competitive strategy applied by Samosa UMKM in Meulaboh, Aceh, using Porter's Five Forces Model approach. The research was conducted using a qualitative method, namely in-depth interviews to gain a comprehensive understanding of various aspects of the business which include the company's vision and mission, marketing strategy, operational management, product innovation, as well as competition and market dynamics. The results revealed that Samosa UMKM rely on a strong digital marketing strategy through social media platforms and maintain a focus on product quality as a competitive advantage. The main challenges faced by the company are difficulties in recruiting and retaining quality employees as well as economic instability that affects consumer purchasing power. Nonetheless, the company has promising growth prospects through product innovation and market expansion opportunities to other regions. The conclusion of this study shows that an effective digital marketing strategy and consistency in product quality are the main factors that support the competitiveness of Samosa UMKM. However, to face increasingly fierce competition, further efforts are needed in product diversification as well as more targeted market segmentation in order to expand market share and maintain business growth